2021
DOI: 10.7759/cureus.14106
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cost-Effectiveness of Interscalene Brachial Plexus Block With Sedation in Reverse Total Shoulder Replacement

Abstract: Aims To investigate the safety and cost-effectiveness of interscalene brachial plexus block/regional anaesthesia (ISB-RA) in patients undergoing reverse total shoulder replacement. Patients and methods This retrospective study included 15 patients with symptomatic rotator cuff arthropathy who underwent reverse total shoulder arthroplasty (rTSA) under ISB-RA without general anaesthesia in the beach chair position from 2010 to 2018. The mean patient age was 77 years (range 59-82 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Health economic evaluation in the field of anesthesia is increasingly used for decision-making and has become a relevant component of healthcare system programs worldwide [1]. However, little is known about the economic impact of regional anesthesia [2] in general and, even less, about that of the brachial plexus block in particular [1,[3][4][5][6]. As far as the latter is concerned, the economic outcomes reported in the literature are either rather heterogeneous [1,5,6] or evaluate obsolete regional anesthesia techniques [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health economic evaluation in the field of anesthesia is increasingly used for decision-making and has become a relevant component of healthcare system programs worldwide [1]. However, little is known about the economic impact of regional anesthesia [2] in general and, even less, about that of the brachial plexus block in particular [1,[3][4][5][6]. As far as the latter is concerned, the economic outcomes reported in the literature are either rather heterogeneous [1,5,6] or evaluate obsolete regional anesthesia techniques [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the economic impact of regional anesthesia [2] in general and, even less, about that of the brachial plexus block in particular [1,[3][4][5][6]. As far as the latter is concerned, the economic outcomes reported in the literature are either rather heterogeneous [1,5,6] or evaluate obsolete regional anesthesia techniques [4]. In the only randomized clinical trial assessing the economics of ultrasound-guided interscalene block in arthroscopic shoulder surgery published to date, Gonano et al concluded that interscalene block, as solo anesthesia, is a cost-effective technique as compared with general anesthesia [3].…”
Section: Introductionmentioning
confidence: 99%